Biofilm Formation by Uropathogens and Its Impact on Antimicrobial Susceptibility Pattern - Priyanka Sharma; Sandeep Dogra; Bella Mahajan; Shashi Sudhan Sharma (Universitas Ahmad Dahlan, 2022)
Background: Out of all Hospital-Associated Infections (HAIs),Urinary Tract Infection (UTI) is the second most common infection that accounts for approximately 34%, and 80% are associated with indwelling catheters and hence with biofilm formation, which invites multi-drug resistant microorganisms. The present study was designed to study in-vitro biofilm forming uropathogens and their antimicrobial susceptibility in a tertiary care hospital in north India. Method:The present cross-sectional study consisted of 200 urine specimens collected over one year from patients with symptoms of urinary tract infection. Following their isolation and identification, all the isolates were subjected to screening for biofilm formation by Congo Red Agar (CRA) and the Tube Adherence (TA) methods. Subsequently, the Kirby Bauer-disk diffusion method performed the antimicrobial susceptibility test. Results: Out of the total samples (n = 200), a total of 46 (23%) were positive by the CRA method, while 33 (16.5%) were positive by the TA method. Twenty-one (21%) isolates came positive by both methods. Biofilm formation was seen more commonly in females (82%). Biofilm-forming uropathogens develop significantly higher resistance to antimicrobial drugs than non-producers. Conclusion: The correlation was significant between biofilm production and multidrug resistance. Also, it was concluded that the CRA method could be employed to detect biofilm formation in resource-limited countries.